The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1289/ehp.10271
|View full text |Cite
|
Sign up to set email alerts
|

Life-Span Exposure to Low Doses of Aspartame Beginning during Prenatal Life Increases Cancer Effects in Rats

Abstract: BackgroundIn a previous study conducted at the Cesare Maltoni Cancer Research Center of the European Ramazzini Foundation (CMCRC/ERF), we demonstrated for the first time that aspartame (APM) is a multipotent carcinogenic agent when various doses are administered with feed to Sprague-Dawley rats from 8 weeks of age throughout the life span.ObjectiveThe aim of this second study is to better quantify the carcinogenic risk of APM, beginning treatment during fetal life.MethodsWe studied groups of 70–95 male and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 17 publications
6
155
1
8
Order By: Relevance
“…The authors state, based on the results of their study, that aspartame induces cancer in the livers and lungs of male Swiss mice, reiterating their previous conclusions that aspartame is a carcinogenic agent in rodents (Soffritti et al, 2006(Soffritti et al, , 2007. Halldorsson et al (2010) investigated preterm delivery in a cohort of 59 334 pregnant Danish women.…”
Section: Assessment 1 Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors state, based on the results of their study, that aspartame induces cancer in the livers and lungs of male Swiss mice, reiterating their previous conclusions that aspartame is a carcinogenic agent in rodents (Soffritti et al, 2006(Soffritti et al, , 2007. Halldorsson et al (2010) investigated preterm delivery in a cohort of 59 334 pregnant Danish women.…”
Section: Assessment 1 Introductionmentioning
confidence: 94%
“…In its scientific statement, the ANS Panel has indicated that it will undertake a detailed analysis of the study results and conclusions reported by Soffritti et al (2010), including the suggested implication of methanol. ) on a further ERF study investigating the effects of a life-span exposure to low doses of aspartame in rats (Soffritti et al, 2007). This opinion also took into consideration additional data submitted by the Ramazzini Foundation in February 2009.…”
Section: Assessment 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors state: ''In the last 20 years, the overall incidences of lymphomas/leukemias in [ERF] control rats were reported to be 20.6% (range 8.0-30.9%) among 2,265 male rats and 13.3% (range 4.0-25%) among 2,274 female rats [Soffritti et al, 2007]. Thus, even for lifetime studies, the incidences of lymphomas/ leukemias in the ERF bioassay are relatively low and stable across studies, generally allowing for discernment of treatment-related effects.''…”
Section: To the Editormentioning
confidence: 99%
“…Asimismo, el estudio en ratas demostró que la exposición prenatal al aspartame aumenta los efectos carcinogenéticos (Sofritti et al, 2007). Vale la pena señalar que dichos estudios insumen periodos de ensayo que muchas veces exceden la vida del animal, es decir que la manifestación clínica del cáncer que se observa hoy en una persona responde a una exposición al tóxico que data de 20 a 30 años.…”
Section: Introductionunclassified